PERLINDUNGAN HUKUM TERHADAP PENGGARAP TANAH DI ATAS TANAH NEGARA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR: 1401 K/ Pdt/ 2018) - Shella Aprillia; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
Lands, which are physically possessed by residents who do not convert their western land rights after the enactment of the Basic Agrarian Law, becomes state land directly controlled by the state, which is then issued a certificate of building rights in the name of PT. Asuransi Jiwasraya (Persero). How is the legal protection for cultivators on state land with the issuance of certificates in the name of PT. Jiwasraya Insurance? The researcher examined this problem using a normative legal research method; the data collection technique includes observation, data collection and interviews; the research approach used was statutory approach; and the data analysis technique used was vertical to horizontal synchronization. The research data reveals the existence of weaknesses and legal errors in the application of the case. As a result, the land which has been controlled by the residents for 73 years has changed ownership to PT. Asuransi Jiwasraya (Persero), which in fact should have been owned by the residents.